Influencia de la aplicación de dos tipos de levaduras y el tiempo de fermentación, en la calidad organoléptica de taza de Coffea arabica var. Típica de la finca Agroloja - Barba Rios, Cristina Elizabeth (2023)
The research was carried out at Agroloja farm, located in the Malacatos, province of Loja, taking into account that the province is the main producer of coffee in Ecuador. The importance of this work lay in the relationship between the application of yeasts and fermentation time, and how these influence the quality attributes in the sensory analysis of coffee in the Típica variety. The use of yeasts in the coffee fermentation process is a topic of increasing importance in recent years, so it is necessary to know their positive effects on organoleptic characteristics. To carry out the study, 80 kg of cherry were harvested, which was subsequently pulped to carry out the fermentation process. The behavior of two strains of yeasts of Saccharomyces cerevisiae (S-04 and WB-06) commonly used in the fermentation of beer wort was evaluated. The application was carried out in two stages of 4 and 6 days in anaerobic fermentation, in wet processing method. The pH and °Bx variables were measured at the beginning and end of the fermentation process. In the results obtained it was observed that the decreasing trend of these two variables was a function of the yeast strain and time, the most notable reduction in pH was observed in the S-04 strain in both times, and for the variable °Bx the greatest reduction occurred with the WB-06 strain at 6 days. The sensory analysis was performed by three certified tasters, who evaluated the organoleptic characteristics of the coffee: fragrance/scent, flavor, body, acidity, uniformity, clean cup and taster score; also, primary and secondary defects were determined. Results showed that the sample T5 obtained the best score with the strain WB-06 and a fermentation for 6 days, with a score of 87.33, which was characterized with fruity and citrus notes among the main ones. It is concluded that the addition of Saccharomyces cerevisiae positively influenced the improvement of the organoleptic characteristics of cup quality and when comparing the treatments of the research with the control, it was observed that the addition of S. cerevisiae significantly influenced the cup quality scores with values higher than 84 points, cataloging them as specialty coffees. Key words: Saccharomyces cerevisiae, anaerobic fermentation, drying, wet processing method, cupping.